Life Expectancy and Income Convergence in the World. - Ueda, Kenichi (IMF Working Papers., 2008)
There is world-wide convergence in life expectancy, despite little convergence in GDP per capita. If one values longer life much more than material happiness, the world living standards may this have already converged substantially. This paper introduces the concept of the dynastic general equilibrium value of life to measure welfare gains from the increase in life expectancy. A calibration study finds sizable welfare gains, but these gains hardly mitigate the large inequality among countries. A conventional GDP-based measure remains a good approximation for (non) convergence in world living s.